1991
DOI: 10.1073/pnas.88.14.6186
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of matrin F/G: A DNA binding protein of the nuclear matrix that contains putative zinc finger motifs.

Abstract: We have isolated a 2.7-kilobase rat liver cDNA clone that contains the entire 544-amino acid coding sequence for matrin F/G. This protein has previously been localized to the internal, fibrogranular areas of the nuclear matrix and shown to bind to DNA on nitrocellulose blots. The predicted amino acid sequence from the coding region of this cDNA shows that this protein contains -50% hydrophobic amino acids with secondary structure predictions suggesting a large percentage of fl-sheet regions. No significant hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 39 publications
0
27
1
1
Order By: Relevance
“…Sequence analysis of a corresponding cDNA derived from a HUVEC library initially revealed a novel gene that was homologous to a gene encoding the rat matrin F/G. 12,13 Subsequently, Kanai and colleagues 7 reported a longer reading frame within the rat matrin F/G cDNA and demonstrated that this longer form of the protein encoded a member of the family of 12-membrane-spanning transporters that was capable of specifically transporting prostaglandins. This group then identified the human homolog of this molecule and named it hPGT (for human prostaglandin transporter).…”
Section: Identification Of Hpgt As a Regulated Gene In Cultured Vascumentioning
confidence: 99%
“…Sequence analysis of a corresponding cDNA derived from a HUVEC library initially revealed a novel gene that was homologous to a gene encoding the rat matrin F/G. 12,13 Subsequently, Kanai and colleagues 7 reported a longer reading frame within the rat matrin F/G cDNA and demonstrated that this longer form of the protein encoded a member of the family of 12-membrane-spanning transporters that was capable of specifically transporting prostaglandins. This group then identified the human homolog of this molecule and named it hPGT (for human prostaglandin transporter).…”
Section: Identification Of Hpgt As a Regulated Gene In Cultured Vascumentioning
confidence: 99%
“…The resulting NM was washed with the extraction buffer. Isolation of the NM was verified by the removal of DNA (DAPI staining) and retention of matrin-3 protein, known to be concentrated in the NM (Hakes and Berezney, 1991).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Most likely, this association is mediated by defined proteins that specifically bind to MAR/SARs. A number of proteins that fulfill this definition have been identified, characterized, and cloned (2,9,10,15,25,28,46,47,52). While some MAR-binding proteins seem to have additional roles in RNA processing and transport, others function mainly as structuring proteins at the level of higher-order chromatin organization.…”
mentioning
confidence: 99%